#1**+1 **

\(y=-12\)

\(5(y+2)=2(2y-1)\) | This is the given equation. First, distribute the 5 and 2 |

\(5y+10=4y-2\) | Subtract 4y on both sides |

\(y+10=-2\) | Subtract 10 on both sides |

\(y=-12\) | We found y, so we are done! |

If you are ever unsure whether or not your answer is correct, plug the y-value into the equation. Then, check to see that the equation is true:

\(5(-12+2)=2(2(-12)-1)\) | Check to see if this is true by simplifying. Let's clean this up |

\(5*-10=2(-24-1)\) | |

\(5*-10=2*-25\) | |

\(-50=-50\) | This is true, so the answer, y=-12 is the correct and only correct solution |

TheXSquaredFactor
May 23, 2017